Advances in carbohydrate chemistry and biochemistry. - Horton, Derek, 1932- (Advances in carbohydrate chemistry and biochemistry, 1995)
Since its inception in 1945, this serial has provided critical articles by research specialists in the industrial, analytical, and technological aspects of biochemistry, organic chemistry, and instrumentation methodology. The articles provide a definitive interpretation of the current status and future trends in carbohydrate chemistry and biochemistry.